2005
DOI: 10.4049/jimmunol.174.11.7234
|View full text |Cite
|
Sign up to set email alerts
|

Role for Innate IFNs in Determining Respiratory Syncytial Virus Immunopathology

Abstract: Respiratory syncytial virus (RSV) is the major cause of severe lower airway disease in infants and young children, but no safe and effective RSV vaccine is yet available. The difficulties involved in RSV vaccine development were recognized in an early vaccine trial, when children immunized with a formalin-inactivated virus preparation experienced enhanced illness after natural infection. Subsequent research in animal models has shown that the vaccine-enhanced disease is mediated at least in part by memory cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
58
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(68 citation statements)
references
References 50 publications
9
58
1
Order By: Relevance
“…At either time point, vvF-immunized mice harbored less virus than mice undergoing a primary RSV infection. Our plaque assay data support previous work with IFN-␥ receptor-deficient mice on the 129SvEv background showing that viral clearance after primary infection is not dependent upon IFN-␥ signaling (5,24). These data indicate that IFN-␥ deficiency does not alter viral clearance and suggest that viral load would be reduced upon inclusion of the F protein in future RSV vaccines.…”
Section: Vol 82 2008 Role Of Ifn-␥ During Rsv Vaccine-enhanced Disesupporting
confidence: 80%
“…At either time point, vvF-immunized mice harbored less virus than mice undergoing a primary RSV infection. Our plaque assay data support previous work with IFN-␥ receptor-deficient mice on the 129SvEv background showing that viral clearance after primary infection is not dependent upon IFN-␥ signaling (5,24). These data indicate that IFN-␥ deficiency does not alter viral clearance and suggest that viral load would be reduced upon inclusion of the F protein in future RSV vaccines.…”
Section: Vol 82 2008 Role Of Ifn-␥ During Rsv Vaccine-enhanced Disesupporting
confidence: 80%
“…These data demonstrate that IFNAR signaling contributes to the limitation of both the replication and the spread of HMPV, similar to what has been observed in related viruses (47)(48)(49)(50). One group found that both type I and II IFNs are important for RSV in BALB/c mice (50,51).…”
Section: Discussionsupporting
confidence: 60%
“…6C). IL-13 was chosen as an indicator of Th2 cytokine production, as this cytokine was previously found to predominate following RSV infection in STAT1 Ϫ/Ϫ mice, which lack the ability to generate a Th1 response (33). As observed in the lung samples taken at 4 days postchallenge, IFN-␥ production by splenocytes derived from mice previously infected with RSV was not significantly enhanced compared to cultures from mock-immunized animals.…”
Section: Vol 80 2006 Recombinant Ndv As a Vaccine Vector For Rsv 1133mentioning
confidence: 81%